2013
DOI: 10.1186/1477-7819-11-206
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic tumor with extensive involvement of the bladder in an adolescent: a case report

Abstract: Inflammatory myofibroblastic tumor (IMT) is a rare lesion of unclear pathogenesis that shows a wide, highly variable spectrum of clinical behavior. We describe the case of a 17-year-old boy with a large IMT that infiltrated the bladder, ileocecal junction, peritoneum and pelvic retroperitoneal space. The tumor was associated with extensive toughening and thickening of the bladder, and, although it showed a tendency for invasive growth, it affected mainly the bladder and adjacent tissue. To the best of our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Tumors affecting this site usually appear as polypoid intraluminal or submucosal masses with or without extension into the perivesical fat [ 138 ], although a tough, diffuse lesion featuring uneven thickening of the bladder has been described [ 139 ]. Histologically, inflammatory myofibroblastic tumor is characterized by a proliferation of spindled cells arranged in cellular fascicles admixed with inflammatory cells including plasma cells, and lymphocytes.…”
Section: Inflammatory Myofibroblastic Tumor (Imt)mentioning
confidence: 99%
“…Tumors affecting this site usually appear as polypoid intraluminal or submucosal masses with or without extension into the perivesical fat [ 138 ], although a tough, diffuse lesion featuring uneven thickening of the bladder has been described [ 139 ]. Histologically, inflammatory myofibroblastic tumor is characterized by a proliferation of spindled cells arranged in cellular fascicles admixed with inflammatory cells including plasma cells, and lymphocytes.…”
Section: Inflammatory Myofibroblastic Tumor (Imt)mentioning
confidence: 99%
“…The IMTUB invaded the peritoneum, ileocecal junction, greater omentum, appendix, and other tissues in two reported cases (12,23). Encouragingly, there was no local recurrence or distant metastasis in either adolescent after 6-12 months (12,23). The tumor may be characterized by aggressive growth if it extends to tissues outside the bladder, such as the peritoneum, greater omentum, and ileocecal region.…”
Section: Discussionmentioning
confidence: 93%
“…Concerning genes, IMT may be more related to the clonal chromosomal rearrangement of ALK than PSCN. Leiomyosarcomas and sarcomatoid carcinomas usually lack ALK expression, especially when necrosis is present ( 2 , 12 , 13 ). A meta-analysis indicated that ALK played an important role in diagnosing and distinguishing IMTUB ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, among the children’s laryngeal IMT reports, the only ALK-positive case had no recurrence, and the one recurrent case was ALK-negative [ 4 , 7 ]. In other anatomic locations, there are many reports of ALK-negative IMTs showing invasive biological behavior [ 23 - 25 ]. Accordingly, we think that complete resection of the tumor with negative surgical margins is the key to preventing recurrence.…”
Section: Discussionmentioning
confidence: 99%